Recent Advances in Half-life Extension Strategies for Therapeutic Peptides and Proteins - Tan, Huanbo; Su, Wencheng; Zhang, Wenyu; Wang, Pengju; Sattler, Michael; Zou, Peijian (Current Pharmaceutical Design, 2018)
Peptides and proteins are two classes of molecules with attractive possibilities for therapeutic applications. However, the bottleneck for the therapeutic application of many peptides and proteins is their short halflives in vivo, typically just a few minutes to hours. Half-life extension strategies have been extensively studied and many of them have been proven to be effective in the generation of long-acting therapeutics with improved pharmacokinetic and pharmacodynamic properties. In this review, we summarize the recent advances in half-life extension strategies, illustrate their potential applications and give some examples, highlighting the strategies that have been used in approved drugs and for drugs in clinical trials. Meanwhile, several novel strategies that are still in the process of discovery or at a preclinical stage are also introduced. In these strategies, the two most frequently used half-life extension methods are the reduction in the rate of renal clearance or the exploitation of the recycling mechanism of FcRn by binding to the albumin or IgG-Fc. Here, we discuss half-life extension strategies of recombinant therapeutic protein via genetic fusion, rather than chemical conjugation such as PEGylation. With the rapid development of genetic engineering and protein engineering, novel strategies for half-life extension have been emerged consistently. Some of these will be evaluated in clinical trials and may become viable alternatives to current strategies for making next-generation biodrugs.
Keywords: Peptides and proteins